Acceleration of the Growth of Islamic Banking in Indonesia - Muhammad Kamal Zubair (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
This paper aims to show the growth of Islamic banking industry in Indonesia. In this time, fast growth of Islamic banking industry progressively is office network side as consequence of improvement of requirement of society and enthusiasm of bank to provide service. In 2008 Bank of Indonesia estimated that Islamic banking industry will enjoy high growth compared to national banking in general. This prediction was based on the finishing Law of Islamic Securities (SBSN) and Law of Islamic Bank (UUPS) and completion of Tax Law.Keywords: bank syariah, growth, Bank of Indonesia